2022
DOI: 10.48101/ujms.v127.7823
|View full text |Cite
|
Sign up to set email alerts
|

Violence and sexual risk taking reported by young people at Swedish youth clinics

Abstract: Background: Early identification of sexual risk taking and exposure to violence is fundamental when seeking to strengthen young people’s health. The purpose of this study was to study factors associated with sexual risk taking and ill health, as well as to study gender differences, and the associations amongst exposure to multiple forms of violence, sexual risk taking and ill health. Methods: This was a cross-sectional study based on data from 3,205 young people answering a questionnaire belonging to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
2
7
0
7
Order By: Relevance
“…Autistic transgender, non-binary, and genderqueer participants were signi cantly more likely to experience sexual violence than autistic cisgender males 37 , and reported severe gendered harassment, exclusion, and threats 92 . These ndings re ect those found among disabled 93,94 and general population research 50,95,96 indicating the heightened vulnerability of gender minorities across various forms of violence. Our ndings are preliminary, but concerning, and warrant further investigation into the nature and risk of violence among autistic gender marginalised groups.…”
Section: Gendersupporting
confidence: 72%
“…Autistic transgender, non-binary, and genderqueer participants were signi cantly more likely to experience sexual violence than autistic cisgender males 37 , and reported severe gendered harassment, exclusion, and threats 92 . These ndings re ect those found among disabled 93,94 and general population research 50,95,96 indicating the heightened vulnerability of gender minorities across various forms of violence. Our ndings are preliminary, but concerning, and warrant further investigation into the nature and risk of violence among autistic gender marginalised groups.…”
Section: Gendersupporting
confidence: 72%
“…However, this shortcoming has been corrected in later versions (SEXIT 2.0 and 3.0). 11,35 Future studies We suggest that future studies should focus on the care and support offered to youth clinic visitors identified as at risk of sexual ill health, the clinical effectiveness of the measures, and how they are perceived and valued by the youth clinic visitors themselves. Exploring healthcare professionals' experiences of using the SEXIT tool kit would also contribute important knowledge.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The phenomenon of sexual risk‐taking and ill health is an urgent issue in Sweden [ 14 , 15 , 16 ] as previous studies report a high prevalence of sexual violence in early adolescence among all genders [ 15 ], but especially among women [ 14 , 16 , 17 ] and transgender young people [ 16 ]. In a Swedish report, women (9.4%) reported experiences of a sexual crime significantly more often than men (1.4%) in 2019 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, male and transgender young people visiting youth clinics report more events of sexual risk‐taking such as multiple sexual partners [ 16 ], and there are also reports of increasing rates of gonorrhoea infections in the youth population [ 18 ]. Overall, this demonstrates a need for knowledge to understand how complex issues such as exposure to violence and experiences of multiple sex partners can be addressed and to identify young people in need of support and care.…”
Section: Introductionmentioning
confidence: 99%